The Search for Truth, with Special Reference to the Frequency of Gastric Ulcer-Cancer and the Origin of Grawitz Tumours of the Kidney: (Section of Pathology) - Newcomb, W. D. (1936)
The importance of the truth in science is emphasized and the difficulty of finding the truth by searching medical literature is pointed out. Two pathological problems are considered as illustrations. The great variation of opinion as to the frequency of ulcer-cancer of the stomach is noted and the lack of definite histological criteria for its diagnosis is suggested as the cause of this variation. Four points in the diagnosis of pre-existing peptic ulcer are mentioned and the importance of fusion between the muscularis mucosæ and muscularis at the edge of the ulcer is insisted upon. The risk of mistaking deep epithelial heterotopia for carcinoma is illustrated. The problem of the origin of Grawitz tumours of the kidney is next considered and the literature briefly reviewed. The rarity of carcinoma of the suprarenal compared with Grawitz tumours is indicated by an examination of 5,201 autopsies at St. Mary's Hospital. The variation in sex incidence of the two tumours is also commented upon. The results of an analysis of 387 small nodules found in the kidneys in 1,172 necropsies are given. Adenomata were found in 7.2% and accessory suprarenals in 2.6%. An example of a transition between an adenoma and a Grawitz tumour is illustrated. Stress is laid on the essential papillary structure of the Grawitz tumour and it is suggested that the renal theory of its origin is more likely to be true.